Island apart [large type] - Raichlen, Steven (Thorndike Press, 2012)
Claire Doheney, recovering from a serious illness, agrees to house-sit in an oceanfront mansion on Chappaquiddick island in Martha's Vineyard. The New York book editor hopes to find solace, strength, and sufficient calm to finish her biography of the iconoclastic psychotherapist, Wilhelm Reich. The last thing she expects to find is love. Then she meets a mysterious man the locals call the Hermit. No one knows his real name or where he lives. To their mutual surprise, Claire and the stranger discover that they share a passion for cooking that soon sparks something more. But Claire's new friend has a terrible secret that threatens to drive them apart forever. The clock is ticking. Can Claire let love into her life once more before it's too late?